Revealing the Specific Regulations of Brassinolide on Tomato Fruit Chilling Injury by Integrated Multi-Omics - Bai, Chunmei; Zheng, Yanyan; Watkins, Christopher B.; Fu, Anzhen; Ma, Lili; Gao, HongWu; Yuan, Shuzhi; Zheng, Shufang; Gao, Lipu; Wang, Qing; Meng, Demei; Zuo, Jinhua (Frontiers in Nutrition, 2021)
Tomato fruit are susceptible to Chilling Injury (CI) when stored at low temperature, limiting storage potential and resulting in economic loss if inappropriate temperatures are used. Brassinolide (BR) is a plant growth regulator that is known to decrease susceptibility of fruit to CI. In this study, transcriptome, metabolome and proteome analyses were carried out on tomato fruit with or without BR treatment stored at 0 ℃. Pericarp tissues were sampledon days 0 and 8. Differentially expressed genes (DEGs), differentially expressed metabolites (DEMs) and differentially expressed proteins (DEPs) were affected by BR treatment. Screening and analysis revealed that many key enzymes and transcription factors, such as peroxidase (POD), cellulose synthase (CeSA), pectin acetylesterase (PAE), lipoxygenase (LOX), EIN3-Binding F-box Protein 1, ethylene responsive factor (ERF), GATA transcription factors (TFs), TCP transcription factor (TFs) and basic-helix-loop-helix 3 (bHLH3), associated with low storage temperature were alleviated by BR. The genes, metabolites and proteins affected by BR treatment are primarily related to in plant hormone signal transduction, carotenoid, phenylpropanoid and amino acid biosynthesis.